Non-neoplastic hematopathology and infections - Cualing, Hernani D.; Bhargava, Parul; Sandin, Ramon L. (Hoboken : John Wiley & Sons, 2012)
Most books on hematopathology are neoplastic in scope and offer little non-neoplastic content. In Non-Neoplastic Hematopathology and Infections, the authors fully describe the hematologic manifestations in tissue and blood of infectious agents, including many rare and exotic diseases found in both Western and Eastern hemispheres, in order to assist pathologists and medical laboratory professionals all over the world in better diagnosing and treating such infections. Thoroughly illustrated with photographs, tables and text, this book features a wide range of non-neoplastic hematologic disorders.
Non-Neoplastic Hematopathology and Infections; CONTENTS; Contributors; Foreword; Preface; Acknowledgments; Introduction; PART I Non-neoplastic Hematology; CHAPTER ONE Non-neoplastic Disorders of White Blood Cells; Overview of WBC Production and Function; Leukocytes; Leukemoid Reaction; Left Shift; Quantitative Disorders of WBCS; Disorders of Neutrophils; Disorders of Lymphocytes; Disorders of Plasma Cells; Disorders of Monocytes; Disorders of Eosinophils; Disorders of Basophils; Qualitative Disorders of WBCS; Congenital Disorders of Leukocytes; Acquired Disorders of Leukocytes; References.
Includes bibliographical references.
Print version record.
Keywords: Infection; Blood -- Diseases; Hematologic Diseases -- pathology; Infection -- pathology; MEDICAL -- Hematology; Blood -- Diseases; Infection; Electronic books